Women’s Fashion Simulacra A Compulsive Narrative in Syahrini’s Shopee Advertisement - Irwanto, Irwanto; Hariatiningsih, Laurensia Retno; Soraya, Iin; El Hidayah, Nur Iman; Ningtyas, Dito Anjasmoro (Unisba Press, 2022)
Advertising is essential in persuading, strengthening, and reminding the product of the public. Advertising is a representation of a product. From the modern communication perspective, advertising is used to make up the product's image. Recently, advertisements have appeared not only in conventional media but also in new media. Advertising works are becoming more varied and creative considering that new media are relatively uptight regulation than conventional media. This creates a hyper-reality that goes beyond the function of the ad itself. This study seeks to reveal Syahrini's Shopee marketplace advertisement on Youtube. The advertisement's content is examined critically and analyzed using Pierce's triangle of meaning: object, interpretant, and representamen. The research found that hyper-reality simulacra were created as a compulsive shopping narrative. This occurs due to unpleasant events or negative feelings caused by addiction, depression, and boredom. However, the public does not know this.